Acute ketamine challenge increases resting state prefrontal-hippocampal connectivity in both humans and rats - Grimm, Oliver; Sartorius, Alexander; Meyer-Lindenberg, Andreas (Psychopharmacology, 2015)
RationaleAberrant prefrontal-hippocampal (PFC-HC) connectivity is disrupted in several psychiatric and at-risk conditions. Advances in rodent functional imaging have opened the possibility that this phenotype could serve as a translational imaging marker for psychiatric research. Recent evidence from functional magnetic resonance imaging (fMRI) studies has indicated an increase in PFC-HC coupling during working-memory tasks in both schizophrenic patients and at-risk populations, in contrast to a decrease in resting-state PFC-HC connectivity. Acute ketamine challenge is widely used in both humans and rats as a pharmacological model to study the mechanisms of N-methyl-d-aspartate (NMDA) receptor hypofunction in the context of psychiatric disorders.ObjectivesWe aimed to establish whether acute ketamine challenge has consistent effects in rats and humans by investigating resting-state fMRI PFC-HC connectivity and thus to corroborate its potential utility as a translational probe.MethodsTwenty-four healthy human subjects (12 females, mean age 25 years) received intravenous doses of either saline (placebo) or ketamine (0.5 mg/kg body weight). Eighteen Sprague-Dawley male rats received either saline or ketamine (25 mg/kg). Resting-state fMRI measurements took place after injections, and the data were analyzed for PFC-HC functional connectivity.ResultsIn both species, ketamine induced a robust increase in PFC-HC coupling, in contrast to findings in chronic schizophrenia.ConclusionsThis translational comparison demonstrates a cross-species consistency in pharmacological effect and elucidates ketamine-induced alterations in PFC-HC coupling, a phenotype often disrupted in pathological conditions, which may give clue to understanding of psychiatric disorders and their onset, and help in the development of new treatments.